Pengaruh ICT Literacy dan Dukungan Teman Sebaya Terhadap Self Directed Learning Pada Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2022 - Aryanti, Arini; Gumilar, Rendra; Nurdianti, Raden Roro Suci (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research was motivated by the problem of low levels of self-directed learning among students. This research was carried out to determine the influence of ICT literacy and peer support on self-directed learning in students majoring in Economic Education, Class of 2022, partially and simultaneously. This research uses a quantitative survey method. The population in this study were all Economic Education students at the Faculty of Teacher Training and Education, Siliwangi University class of 2022. The sampling technique used was "Saturated Sampling" totaling 134 students. The data collection technique uses a questionnaire and the data analysis technique uses the SPSS 26.0 for Windows program. The research results show that: 1) There is a significant influence of ICT literacy on self-directedness with a significance of 0.000 and a t count of 7.710. Because the significance value of t < 0.05 and t count > t table (7.710 > 1.90839). 2) There is a significant influence of peer support on self-directed learning with a significance of 0.003 and t count of 3.048. Because the significance value of t < 0.05 and t count > t table (3.048 > 1.90839). 3) There is a significant influence of ICT literacy and peer support on self-directed (f test) with a significance value of 0.000 and f count of 64.322. Because the significance value of f < 0.05 and calculated f > t table (63,497 > 1.55).